Temporomandibular Joint Pain: An Unusual Initial Manifestation of Rheumatoid Arthritis - DA Ibrahim; MB Kofar; A Hamidu; TE Adeyemi (Nigerian Dental Association, 2023)
We present a 39-year old housewife with temporomandibular joint pain of more than a month duration prior to the development of symmetrical polyarthritis of the small joints of the hands, as an unusual first manifestation of rheumatoid arthritis.  A raised acute phase reactant such as ESR is a very helpful indicator of an underlying inflammatory condition, hence the need for early referral to the Rheumatologist.